PENGARUH LINGKUNGAN SOSIAL DAN POTENSI DIRI TERHADAP MINAT MELANJUTKAN PENDIDIKAN AKUNTANSI DI PERGURUAN TINGGI - Muhammad Natsir (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2023)
This This study aims to examine and analyze the Social Environment and Self Potential for Interest in Continuing Accounting Education in Higher Education. This type of research is a survey, using the sampling technique of saturated sampling method. The sample in this study was 119 students of class XII, majoring in accounting at the 2nd State Vocational High School, Palu. Data collection technique by distributing questionnaires directly to respondents while the method of analysis used is multiple linear regression. The results of this study indicate that the social environment and self-potential simultaneously have a positive and significant effect on interest in continuing education of accounting in higher universities. The social environment partially has a positive and significant effect on interest in continuing education of accounting in higher universities. Self Potential partially has a positive and significant effect on interest in continuing education of accounting in higher universities.